Elektroencefalografie - Jarošová, Veronika (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2012)
Tato semestrální práce má za svůj cíl popsat elektroencefalografii. Začátek práce je věnován historii elektroencefalografie, poté je popsána spontánní i evokovaná aktivita mozku. Dále se zabývá elektroencefalografii. Závěr teoretické části je věnován metodice a zpracování elektroencefalografického signálu. Praktická část práce je zaměřená na vytvoření tří různých úloh na epilepsii, reflexy a paměť. Poté byly úlohy prakticky ověřeny na čtrnácti dobrovolnících. Dále je v práci uveden návod pro daná měření, výsledky hodnocení a jejich diskuze.

This semestral paper has its aim to describe the electroencephalography. The beginning of paper is devoted to the history of electroencephalography, then there is both spontaneous and evoked brain activity described. Further, the paper deal with the electroencephalography. At the conclusion of teoretical part is described the methodology and processing of electroencephalography signal. The practical part of the work is focused on the creation of three various exercises on the epilepsy theme, reflexes and memory. Then the exercises were verified practically at fourteen volunteers. Further, in the work there is mentioned the instruction for particular measures, valuation results and its discussion.
Electroencephalography
Keywords: Elektroencefalografie; EEG; aktivita mozku; artefakty; EEG biofeedback; Electroencephalography; EEG; brain activity; artifacts; EEG biofeedback